2014
DOI: 10.1089/thy.2014.0029
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Subclinical Hypothyroidism, Thyroid Autoimmunity, and the Risk of Miscarriage: A Prospective Cohort Study

Abstract: Background: Increasing data suggest that subclinical hypothyroidism (SCH) and thyroid autoimmunity (TAI) are associated with adverse pregnancy outcomes, but there are limited data on the association of these conditions in early pregnancy with subsequent miscarriage. Methods: In this prospective cohort study, we screened 3315 women at low risk for thyroid dysfunction at four to eight weeks' gestation from iodine-sufficient areas of China between January 2012 and September 2012. Thyrotropin (TSH), free thyroxine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
162
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(174 citation statements)
references
References 28 publications
4
162
1
7
Order By: Relevance
“…On the other hand, in several studies, patients with positive TgAb and/or TPOAb tended to show a high miscarriage rate [12][13][14]. However, in our study, we could not observe such a tendency.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, in several studies, patients with positive TgAb and/or TPOAb tended to show a high miscarriage rate [12][13][14]. However, in our study, we could not observe such a tendency.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the existence of diffuse non-toxic goiter increases the possibility of spontaneous abortion more than by five times (OR 5.6 %; 95 % CI 1.3-22.9) that corresponds to the literature data [2,5,9] about the fact that dysfunction of thyroid holds the first place among the causes of pregnancy miscarriage.…”
Section: Resultssupporting
confidence: 81%
“…Multiple studies have reported an association of SCH with an increase in the risk of adverse pregnancy and neonatal outcomes, including pregnancy loss, preterm delivery, gestational diabetes, gestational hypertension, preeclampsia, placental abruption, premature rupture of membranes, intrauterine growth restriction, low birth weight, small for gestational age, low Apgar score, and neonatal death (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Furthermore, high TSH levels in women during pregnancy have been associated with an increased risk of neurocognitive deficits in the offspring (17).…”
mentioning
confidence: 99%